Identification of a DMBT1 polymorphism associated with increased breast cancer risk and decreased promoter activity - Tchatchou, Sandrine; Riedel, Angela; Lyer, Stefan; Schmutzhard, Julia; Strobel-Freidekind, Olga; Gronert-Sum, Sabine; Mietag, Carola; D'Amato, Mauro; Schlehe, Bettina; Hemminki, Kari; Sutter, Christian; Ditsch, Nina; et al. (Human mutation, 2010)
According to present estimations, the unfavorable combination of alleles with low penetrance but high prevalence in the population might account for the major part of hereditary breast cancer risk. Deleted in Malignant Brain Tumors 1 (DMBT1) has been proposed as a tumor suppressor for breast cancer and other cancer types. Genomewide mapping in mice further identified Dmbt1 as a potential modulator of breast cancer risk. Here, we report the association of two frequent and linked single-nucleotide polymorphisms (SNPs) with increased breast cancer risk in women above the age of 60 years: DMBT1 c.-93C>T, rs2981745, located in the DMBT1 promoter; and DMBT1 c.124A>C, p.Thr42Pro, rs11523871(odds ratio [OR]=1.66, 95% confidence interval [CI]=1.21-2.29, P=0.0017; and OR=1.66; 95% CI=1.21-2.28, P=0.0016, respectively), based on 1,195 BRCA1/2 mutation-negative German breast cancer families and 1,466 unrelated German controls. Promoter studies in breast cancer cells demonstrate that the risk-increasing DMBT1 -93T allele displays significantly decreased promoter activity compared to the DMBT1 -93C allele, resulting in a loss of promoter activity. The data suggest that DMBT1 polymorphisms in the 5′-region are associated with increased breast cancer risk. In accordance with previous results, these data link decreased DMBT1 levels to breast cancer risk. Hum Mutat 30:1-7, 2009. © 2009 Wiley-Liss, Inc.
Erstmals am 14 October 2009 online veröffentlicht
Gesehen am 26.10.2023